2015
DOI: 10.1590/1414-431x20154499
|View full text |Cite
|
Sign up to set email alerts
|

Time-course effects of aerobic exercise training on cardiovascular and renal parameters in 2K1C renovascular hypertensive rats

Abstract: Exercise training (Ex) has been recommended for its beneficial effects in hypertensive states. The present study evaluated the time-course effects of Ex without workload on mean arterial pressure (MAP), reflex bradycardia, cardiac and renal histology, and oxidative stress in two-kidney, one-clip (2K1C) hypertensive rats. Male Fischer rats (10 weeks old; 150–180 g) underwent surgery (2K1C or SHAM) and were subsequently divided into a sedentary (SED) group and Ex group (swimming 1 h/day, 5 days/week for 2, 4, 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
1
14
0
5
Order By: Relevance
“…In previous studies we found that rats with renovascular hypertension (2K1C) submitted to swimming training showed reversal of altered cardiovascular parameters, reduced collagen deposition in the myocardium and the kidneys, reduced TBARS concentration in the left ventricle, and increased CAT activity in the left ventricle and kidney [16]. In the present study, PT improved the physical fitness of rats with MS, as shown by the decrease in the blood concentration of lactate and in the HR.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In previous studies we found that rats with renovascular hypertension (2K1C) submitted to swimming training showed reversal of altered cardiovascular parameters, reduced collagen deposition in the myocardium and the kidneys, reduced TBARS concentration in the left ventricle, and increased CAT activity in the left ventricle and kidney [16]. In the present study, PT improved the physical fitness of rats with MS, as shown by the decrease in the blood concentration of lactate and in the HR.…”
Section: Discussionsupporting
confidence: 73%
“…Different lines of evidence suggest that regular PT induces beneficial adaptations in diseases associated with oxidative stress, including high blood pressure, type II diabetes and Alzheimer's disease [3,16,17]. In previous studies we found that rats with renovascular hypertension (2K1C) submitted to swimming training showed reversal of altered cardiovascular parameters, reduced collagen deposition in the myocardium and the kidneys, reduced TBARS concentration in the left ventricle, and increased CAT activity in the left ventricle and kidney [16].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, Maia et al. (2015) suggested that blood pressure reduction occurs up to week 4 of exercise training. According to these authors, from week 6 to week 10, the blood pressure levels in the 2K1C animals submitted to exercise become similar to those observed in the sedentary 2K1C rats.…”
Section: Discussionmentioning
confidence: 99%